Long‐term safety of adalimumab in clinical trials in adult patients with Crohn's disease or ulcerative colitis. Issue 2 (21st November 2017) - Colombel, J.‐F.; Sandborn, W. J.; Reinisch, W.; Peyrin‐Biroulet, L.; Panaccione, R.; Rutgeerts, P.; Hanauer, S. B.; Ghosh, S.; Van Assche, G.; Robinson, A. M.; Lau, W.; Maa, J.‐F.; et al.
Summary: Background: Adalimumab is used to treat moderate to severe Crohn's disease (CD) and ulcerative colitis (UC) when conventional therapies fail. Aim: To update long‐term adalimumab safety from CD and UC trials; the previous report was CD only, 3160 patients/3402 patient‐years (PYs). Methods: Treatment‐emergent adverse events (AEs; first dose to 70 days after last dose/December 31, 2015) in adults in phase 2/3 and 3/3b trials and open‐label extensions were coded using Medical Dictionary for Regulatory Activities (MedDRA‐v18.1). Rates were assessed as events/100 (E/100 PYs). Results: The database (16 trials; CD, N = 3606; UC, N = 1739) represented 4145 and 3397 PYs of exposure, respectively. For CD, incidences of any AEs with adalimumab were 60.8%‐65.1%, depending on dose, and 71.5% with placebo; for UC, the incidences were 53.5%‐54.8% and 56.1%, respectively. Rates of any AEs (CD, 605 E/100 PYs; UC, 361 E/100 PYs), serious AEs (CD, 36.1 E/100 PYs; UC, 18.9 E/100 PYs), and malignancies (CD, 1.2 E/100 PYs; UC, 1.0 E/100 PYs) were similar between current and prior analyses. Apparent rate of opportunistic infections was lowered to 0.3 and 0.2 E/100 PYs for CD and UC, respectively, by recent MedDRA changes excluding oral candidiasis and tuberculosis. Standardised incidence ratios for malignancies were similar to the general population (CD, 1.45 [95% CI, 0.90‐2.22]; UC, 1.36 [95% CI, 0.84‐2.07]). Demyelinating disorders were uncommon (CD, 0.1 E/100 PYs; UC, <0.1 E/100 PYs). Conclusions: Patients with moderately to severely active Crohn's disease or ulcerative colitis continued to experience acceptable safety with adalimumab, without new safety signals.